Can mouse clicking be seen as involvement in armed conflict? Some notes on the direct participation in hostilities in cyberspace - Lewandowski, Tomasz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2013)
Contemporary armed conflicts are increasingly based on new technologies. These technologies enable to conduct hostilities from a distance, often eliminate the human factor from the battlefield. Nowadays, cyberspace created by the Internet allows to frame the idea of armed conflict outside the traditional recognition of the fight between belligerent armed forces. This article addresses issues of the direct participation of hostilities in cyberspace. In the first part it discusses technological development and its impact on the activation of the civil factor during armed conflicts. In the second part by analysing the current practice of cyber conflicts it refers to the concept of direct participation in hostilities and its constituent elements as a threshold of harm, direct causation, belligerent nexus at the cybernetic level. The third and final part examines the possibility of the loss of protection, in particular, it addresses the issues related to its temporal nature and the question of means and methods of attacking civilians involved in cyber warfare.